Aimel Priority Directions of The Regional Food Complex Effectiveness Increase - Karkh, Dmitry Andreyevich; Gayanova, Venera Medetovna; Aimel, Filipp (Economy of Regions, 2015)
In the article, the modern trends of management integration as a solution of food and sectoral problems are considered. On the basis of national and foreign experience of development of integration, the classification of integration in economic systems is developed. On the basis of the given classification, the concept of integration is conducted. In the article, much attention is given to the food problem solution, which depends more on the agro-industrial complex based on metaintegration. The leading place of a food complex in the system of agro-industrial complex is caused by a role of food and food raw materials in life of the population of the country. The ratio of the sectors participating in the food production and consumer goods makes the sectoral structure of agro-industrial complex. In the conditions of the resource limitation necessary for the production and food delivery to the domestic market, the role of trade will increase not only in agro-industrial complex, but in all national economy. Also, in this article, the phenomenon of clusters is studied. The attention to clusters as to innovation systems reflects a rising tide of interest of economic science to the questions of economics functioning in regional level and understanding of a role of specific local resources in stimulation of innovative opportunities and competitiveness of small and medium business. Creating a cluster, participants develop the spatial and organizational integrated structure, in interaction of legal entities the status is saved and cooperation provides competitive advantages with other business entities. The role of the state in integration of cluster formations in the Russian Federation is more significant, than in any other country. The state represented by regional authorities actively participates in decision-making process by the business located in its catchment area not only through membership in governing bodies of large joint stock companies.